Flexible Operation of Air Separation Units. Issue 4 (19th July 2021) - Klein, Harald; Fritsch, Philipp; Haider, Patrick; Kender, Robert; Rößler, Felix; Rehfeldt, Sebastian; Freko, Pascal; Hoffmann, Rainer; Thomas, Ingo; Wunderlich, Bernd
Abstract: As part of the Energiewende, the current research on energy‐optimized, flexible operation of air separation units is described. A realistic, pressure‐driven approach for dynamic simulation is presented, which is used to provide a detailed, transient simulation model, a digital twin, of an air separation unit. Extreme operation scenarios, such as start‐up and shutdown of the main heat exchanger, the distillation columns or the entire air separation unit, are described. Since the main heat exchanger experiences repeated temperature changes, its lifetime is investigated in a test rig. The gathered data is used to derive and validate detailed, three‐dimensional simulation models. Abstract : An increasingly volatile energy market requires load‐flexible operation of air separation units. Therefore, a digital twin for dynamic process simulation is presented and a representative heat exchanger under thermal alternating load is investigated in experiment and simulation.